Diversity in critical perspectives in adult education: Conflicts and commonalities - Kyung Hi Kim; Ramon Flecha; Mechthild Hart; Fred Schied; Joye Knight; Sherman Stanage (Adult Education Research Conference, 1994)
The objectives of this symposium are to a) explore the commonality and differences inherent in five distinct critical approaches to the study of adult education: Neo-Marxist, Feminist, Phenomenological, Afrocentricist, and Communicative Modernism (Habermasian Theory), b) examine their impact on the study of adult education, and c) critically examine the role of commitment in bringing about social change through adult education.